THE INFLUENCE OF FOREIGN TOURISM FLOWS ON THE BULGARIAN INDUSTRY - E. Genchev (Trakia Journal of Sciences)
Introduction: The tourism industry is one of the fastest-growing sectors of the world economy. The tourism industry is a very important economic factor for many countries in the world, including Bulgaria. The purpose of the present study was to examine the trends in foreign tourism flows in Bulgaria within the period 2008 – 2018, as well as their influence on the structure of the tourism industry. The tasks established by the author go in several directions: 1. Analysis of the trends in the foreign tourism flow in Bulgaria; 2. Measuring tourism’s contribution to the economy, as well as its effect to the industry’s structure. Material and methods:Data were obtained from Eurostat, the National Statistics Institute, and the World Council of Travel and Tourism, and analysis was by least squares multiple regression. Results:The total effect on the tourist industry in our country is greater than the average for the EU – more than 11%. Conclusion: Our research hypothesis that the tourist flow of people who are not citizens of the EU had a beneficial effect on the number of enterprises and employment rates within the “accommodation activities” sector was supported.